Identifying Five Different Perspectives on the Ecosystem Services Concept Using Q Methodology - Hermelingmeier, Verena; Nicholas, Kimberly A. ; 0000-0002-4756-7851 (Ecological Economics, 2017)
The objective of this paper is to recognize and categorize the various ways that ecosystem services researchers perceive the concept and purpose of ecosystem services (ES). To do so, we employed the discourse analysis approach of Q methodology, where 33 researchers ranked 39 statements on ES derived from the literature. Factor analysis of the Q sorts allowed for the interpretation of five main perspectives on ES: a pragmatic view on nature conservation, seeing ES as useful tool (“Non-Economic Utilitarian”), a strongly value-focused perspective with a skeptical view on ES (“Critical Idealist”), an opposition to a utilitarian approach to nature conservation but seeing ES as more encompassing approach (“Anti-Utilitarian”), a focus on a methodological rather than a critical approach to ES (“Methodologist”), and a rather economic approach to environmental decision-making, in which ES is a useful tool (“Moderate Economist”). We see this plurality as illustrating both the potential of the ES concept to serve as a boundary object for collaboration, but also the threat of ineffective collaboration due to the lack of a common conceptual ground. However, as pluralism can be fruitful if handled transparently, we suggest the need for open dialogue about underlying assumptions when using a value-laden concept like ES.
Keywords: Boundary object; Discourse; Interdisciplinarity; Nature-based solutions; Paradigm; Q methodology